Effect of fiber treatment and nanoclay on the tensile properties of jute fiber reinforced polyethylene/clay nanocomposites - Md. Faruk, Hossen; Sinin, Hamdan; Md. Rezaur, Rahman; Md. Mizanur, Rahman; Fui, Kiew Liew; Josephine, Changhui Lai (Korean Fiber Society, 2015)
The tensile properties of chemically treated jute fiber reinforced polyethylene/clay nanocomposites were investigated. Nanocomposites were prepared using hot press moulding technique by varying jute fiber loading (5, 10, 15 and 20 wt%) for both treated and untreated fibers. Raw jute fibers were chemically treated with benzene diazonium salt to increase their compatibility with the polyethylene matrix. Physical and mechanical properties were subsequently characterized. Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) analysis was utilized to study physical properties. Tensile test was conducted for mechanical characterization. FTIR and SEM study showed interfacial interaction among jute fiber, polyethylene and nanoclay. It was observed that at optimum fiber content (15 wt%), treated composites exhibited improvements in tensile strength and modulus by approximately 20 % and 37 % respectively over the raw ones. On the other hand, this composite exhibited improvements in tensile strength and modulus by approximately 8 % and 15 % respectively over the composites without nanoclay. However, treated jute fiber reinforced composites showed better tensile properties compared with untreated ones and also nanoclay incorporated composites enhanced higher tensile properties compared without nanoclay ones. © 2015, The Korean Fiber Society and Springer Science+Business Media Dordrecht.